To find the numerical equivalent of 9^9 x 9^-6, we can simplify each exponent separately.
First, simplify 9^9:
9^9 = 9 x 9 x 9 x 9 x 9 x 9 x 9 x 9 x 9
= 387,420,489
Next, simplify 9^-6:
9^-6 = 1 / 9^6
= 1 / (9 x 9 x 9 x 9 x 9 x 9)
= 1 / 531,441
≈ 0.0000018816
Now, multiply the two simplified expressions:
9^9 x 9^-6 = 387,420,489 x 0.0000018816 ≈ 729.0000095
Therefore, the numerical equivalent of 9^9 x 9^-6 is approximately 729.
Find the numerical equivalent of 9^9 x 9^-6. Your answer should be written without exponents.
1 answer